2021
DOI: 10.1016/j.jbc.2021.100912
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM reveals conformational flexibility in apo DNA polymerase ζ

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 76 publications
1
24
1
Order By: Relevance
“…This work is aimed to determine the consensus scRev3-RBMs and validate their interactions with scRev7, confirm the 2:1 stoichiometry of the scRev7:Rev3 complex, and investigate the scRev3-mediated scRev7 dimerization in solution. While we have validated the two adjacent RBMs within scRev3, our studies have not confirmed the novel head-to-tail dimerization of scRev7 observed in the recent cryo-EM structures of scPolζ ( 34 , 35 ), instead suggesting that scRev7 lacks the ability to form dimers in solution either alone or when tethered by scRev3-RBMs, which is a property that may have emerged later in evolution.…”
contrasting
confidence: 91%
See 4 more Smart Citations
“…This work is aimed to determine the consensus scRev3-RBMs and validate their interactions with scRev7, confirm the 2:1 stoichiometry of the scRev7:Rev3 complex, and investigate the scRev3-mediated scRev7 dimerization in solution. While we have validated the two adjacent RBMs within scRev3, our studies have not confirmed the novel head-to-tail dimerization of scRev7 observed in the recent cryo-EM structures of scPolζ ( 34 , 35 ), instead suggesting that scRev7 lacks the ability to form dimers in solution either alone or when tethered by scRev3-RBMs, which is a property that may have emerged later in evolution.…”
contrasting
confidence: 91%
“…Although scRev7 binds scRev3 in a 2:1 stoichiometry, we found that scRev7 on its own is a monomer and have yet to obtain any data suggesting that scRev7 can homodimerize in solution when bound to scRev3-RBM12. Recent high-resolution cryo-EM structures corroborate a 2:1 scRev7:scRev3 stoichiometry within scPolζ with each scRev7 protomer binding to scRev3-RBM1 and scRev3-RBM2 regions ( 34 , 35 ). In contrast to hRev7, which forms symmetric head-to-head dimer through the canonical HORMA interface centered around helix αC ( 29 , 47 ), the cryo-EM structures (PDB: 6V8P , 6V93 , 7LXD ) suggest that scRev7 dimerizes asymmetrically in a head-to-tail fashion ( Fig.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations